Comparative impact of implementing the 2013 or 2014 cholesterol guideline on vascular events in a quality improvement network. (April 2016) - Egan, Brent M.; Sutherland, Susan E.; Childers, William F.; Dahlheimer, Ruthanne M.; Helmrich, George A.; Lapeyrolerie, Daryl A.; Markle, Nancy; Murphy, Dennis W.; Simmons, Locke; Davis, Robert A.; Tilkemeier, Peter; Sinopoli, Angelo
Objectives: The Quality and Care Model Committee for a clinically integrated network requested a comparative analysis on the projected cardiovascular benefits of implementing either the 2013 and 2014 cholesterol guideline in a South Carolina patient population. A secondary request was to assess the relative risk of the two guidelines based on the literature. Methods: Electronic health data were obtained on 1, 580, 860 adults aged 21–80 years who had had one or more visits from January 2013 to June 2015; 566, 688 had data to calculate 10-year atherosclerotic cardiovascular disease (ASCVD10 ) risk. Adults with end-stage renal disease ( n = 7852), congestive heart failure ( n = 19, 818), alcohol or drug abuse ( n = 68, 547), or currently on statins ( n = 154, 964) were excluded leaving 315, 508 for analysis. Estimated reduction in ASCVD10 assumed that: (a) moderate-intensity statins lowered low-density lipoprotein cholesterol (LDL-C) by 35% and high-intensity statins by 50%; (b) ASCVD events declined 22% for each 1 mmol/l fall in LDL-C. Results: Among the 315, 508 adults in the analysis, 131, 289 (41.6%) were eligible for statins according to the 2013 guideline and 137, 375 (43.5%) to the 2014 guideline. The 2013 and 2014 guidelines were estimated to prevent 6780 and 5915 ASCVD events over 10 years with: (a) relative risk reductions of 29.0% and 21.8%; (b) absolute risk reductions of 5.2% and 4.3%; (c) number needed-to-treat (NNT) of 19 and 23, respectively. The greater projected cardiovascular protection with the 2013 guideline was largely related to greater use of high-dose statins, which carry a greater risk for adverse events. The literature indicates that the NNT for benefit with high-intensity versus moderate-intensity statins is 31 in high-risk patients with a number needed-to-harm of 47. Conclusions: The 2013 guideline is projected to prevent more clinical ASCVD events and with lower NNTs than the 2014 guideline, yet both have substantial benefit. The 2013 guideline is also expected to generate more adverse events, but the risk-benefit profile appears favor .